2016
DOI: 10.1093/jac/dkw188
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of empirical antifungal therapy in ICU patients using 1,3-β-d-glucan

Abstract: Early discontinuation of empirical echinocandin therapy in high-risk ICU patients based on consecutive negative BDG tests may be a reasonable strategy, with great potential to reduce the overuse of echinocandins in ICU patients. Prospective studies with a higher number of patients are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 29 publications
5
33
0
3
Order By: Relevance
“…In the last decade, strategies including biomarkers [b-D-glucan (BDG) or Candida albicans germ tube antibodies (CAGTA)], surveillance cultures or predictive scores have been investigated not only for starting [7][8][9] but also for discontinuing empirical antifungals. 10,11 Our own data, and those of Nucci et al…”
Section: Introductionsupporting
confidence: 61%
“…In the last decade, strategies including biomarkers [b-D-glucan (BDG) or Candida albicans germ tube antibodies (CAGTA)], surveillance cultures or predictive scores have been investigated not only for starting [7][8][9] but also for discontinuing empirical antifungals. 10,11 Our own data, and those of Nucci et al…”
Section: Introductionsupporting
confidence: 61%
“…None of these studies have shown a survival benefit as none of them have been powered to do so; however, the standard of care at this time is utilizing a clinical prediction rule such as the Candida score [18] or the MSG-01 rule [15] to identify high-risk hosts and then monitor serum biomarkers such as BDG or PCR for biomarkerbased pre-emptive therapy or the clinical prediction rules themselves as triggers for empirical therapy. A recent study has also shown that the negative predictive value of BDG can be used to stop empirical therapy as part of an antifungal stewardship intervention [19].…”
Section: Invasive Candidiasismentioning
confidence: 99%
“…In the challenging scenario of early diagnosis of IC, recent studies have demonstrated the diagnostic value of BDG and CAGTA [19,[38][39][40][41][42]. Although the use of BDG measurement in daily practice for establishing the indication or the withdrawal of ESAT should be defined, recent observational studies [41,42] showed that negativity of the BDG assay may be used as a strategy to discontinue ESAT because of the high sensitivity and negative predictive value of the test.…”
Section: Invasive Candidiasismentioning
confidence: 99%
“…De hecho, recientemente Nucci y cols., publicaron una serie en que pacientes críticos en riesgo de EFI por Candida que habían iniciado empíricamente equinocandinas, en caso de obtener hemocultivos y BDG negativos en muestras sucesivas, suspendieron el antifúngico sin deterioro clínico de los pacientes ni evidencias posteriores de candidemia 32 .…”
Section: Artículo Originalunclassified